2014
DOI: 10.1117/1.jatis.1.1.014004
|View full text |Cite
|
Sign up to set email alerts
|

Improving active space telescope wavefront control using predictive thermal modeling

Abstract: Abstract. Active control algorithms for space telescopes are less mature than those for large ground telescopes due to differences in the wavefront control problems. Active wavefront control for space telescopes at L2, such as the James Webb Space Telescope (JWST), requires weighing control costs against the benefits of correcting wavefront perturbations that are a predictable byproduct of the observing schedule, which is known and determined in advance. To improve the control algorithms for these telescopes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…23 The team, led by M. Mountain, was convened in 2002, following a competitive NASA selection process. In addition to providing scientific support for observatory development through launch and commissioning (e.g., Gersh-Range et al 2012;Perrin et al 2014;Gersh-Range & Perrin 2015;Perrin et al 2016;Laginja et al 2018), the team was awarded 210 hr of Guaranteed Time Observer (GTO) time. This time is being used over the first three JWST observing cycles for studies in three different subject areas: (a) Transiting Exoplanet Spectroscopy (lead: N. Lewis); (b) High Contrast Imaging of Exoplanetary Systems (lead: M. Perrin); and (c) Local Group Proper Motion Science (lead: R. van der Marel).…”
Section: Introductionmentioning
confidence: 99%
“…23 The team, led by M. Mountain, was convened in 2002, following a competitive NASA selection process. In addition to providing scientific support for observatory development through launch and commissioning (e.g., Gersh-Range et al 2012;Perrin et al 2014;Gersh-Range & Perrin 2015;Perrin et al 2016;Laginja et al 2018), the team was awarded 210 hr of Guaranteed Time Observer (GTO) time. This time is being used over the first three JWST observing cycles for studies in three different subject areas: (a) Transiting Exoplanet Spectroscopy (lead: N. Lewis); (b) High Contrast Imaging of Exoplanetary Systems (lead: M. Perrin); and (c) Local Group Proper Motion Science (lead: R. van der Marel).…”
Section: Introductionmentioning
confidence: 99%
“…This results in a conservative example, since in a physical system error Zernike terms are correlated with each other and with temperaturean opportunity for optimized predictive controllers. 36,124,125 For the example plotted, the maximum gradient in focus is ∼1 nm/minute, or approximately the value we expect to be able to control (see Sec. 3.1).…”
Section: Parameterized Disturbancesmentioning
confidence: 57%
“…A range of scientific studies have investigated optimal wavefront sensing and control approaches for large space telescopes, including ultra-stable 6 m telescopes with active primary mirrors, 44 9.2 m space telescopes with formation-flying laser guide stars, [45][46][47] and active space telescopes with predictive thermal modeling. 48 There have been several research missions to test approaches to wavefront control and the TRL of these approaches for future missions. The PICTURE sounding rocket flights in 2011 and 2015 demonstrated piezo-electric fine pointing and poweron of a microelectromechanical systems (MEMS) deformable mirror in space 49,50 and the Deformable Mirror Demonstration Mission CubeSat 51,52 launched in 2020 was a prototype space-Adaptive Optics (AO) system that performed closed-loop wavefront control using a MEMS mirror.…”
Section: History Of Astronomical Space Telescope Researchmentioning
confidence: 99%
“…Prior studies have shown that active wavefront control, including potentially predictive control, can substantially mitigate such drifts; conversely, smart scheduling can minimize how often large thermally-adverse changes in spacecraft attitude occur. 29 The JWST wavefront control operations strategy will strive to keep the telescope wavefront as nearly constant as practical. It should thus be possible to make use of observations that are widely separated in time (weeks to months) as part of a PSF reference library, as is also the case for Hubble.…”
Section: Modeling Wavefront Instabilities From Observatory Thermal Response To Slewsmentioning
confidence: 99%